Two Large, Related, Cryptic Plasmids from Geographically Distinct Isolates of Sulfobacillus thermotolerans - Deane, S. M. (American Society for Microbiology, 2011)
Two large cryptic plasmids (59.2 and 65.9 kb) from isolates of Sulfobacillus thermotolerans from Yellowstone National Park (United States) and the Caribbean island of Montserrat were isolated and sequenced. This analysis revealed a common “backbone” region coding for a potential plasmid stability system plus a nonpheromone conjugation system containing homologues of both type IV and type II (tight adherence, or Tad-like) secretion systems.